Estimating the epidemiological impact of reaching the objectives of the Florida integrated HIV prevention and care plan in Miami-Dade CountyResearch in context - Xiao Zang; Micah Piske; Lia Humphrey; Benjamin Enns; Yi Sui; Brandon D.L. Marshall; William C. Goedel; Daniel J. Feaster; Lisa R. Metsch; Patrick S. Sullivan; Hansel E. Tookes; Bohdan Nosyk (Elsevier, 2023)
Summary: Background: The US Ending the HIV Epidemic (EHE) initiative aims to reduce national HIV incidence 90% by 2030 and to address the disproportionate burden of HIV among different racial/ethnic populations. Florida's state-wide 2022-2026 Integrated HIV Prevention and Care Plan outlines objectives for reaching EHE goals. In Miami-Dade County, we determined the epidemiological impact of achieving the integrated plan's objectives individually and jointly. Methods: We adapted an HIV transmission model calibrated to Miami-Dade County adjusting access to HIV testing, pre-exposure prophylaxis (PrEP) and antiretroviral treatment to model the effects of each objective between 2022 and 2030. We compared two service scale-up approaches: (a) scale-up proportionally to existing racial/ethnic group access levels, and (b) scale-up according to new diagnoses across racial/ethnic groups (equity-oriented). We estimated reductions in new HIV infections by each objective and approach, compared to the EHE's incidence reduction target. Findings: The single most influential strategy was reducing new HIV diagnoses in Hispanic/Latinx men who have sex with men through increased PrEP uptake, resulting in 907/2444 (37.1%) fewer annual new HIV infections in 2030. Achieving all objectives jointly would result in 1537/2444 (62.9%) and 1553/2444 (63.5%) fewer annual new HIV infections with the proportional and equity-oriented approaches, respectively. Interpretation: Achieving the goals of Florida's integrated care plan would significantly reduce HIV incidence in Miami-Dade County; however, further efforts are required to achieve EHE targets. Structural changes in service delivery and a focus on effective implementation of available interventions to address racial/ethnic disparities will be crucial to ending the HIV epidemic. Funding: This work was supported by the National Institutes of Health/National Institute on Drug Abuse grant no. R01-DA041747.